2016
DOI: 10.1016/j.indcrop.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Acidification treatment of lignin from sugarcane bagasse results in fractions of reduced polydispersity and high free-radical scavenging capacity

Abstract: Lignin constitutes up to one-third of the material found in plant cell walls and is considered the second most abundant natural polymer in the world. Despite unique characteristics of lignin, it is mostly used for low-value commercial applications. In this study, lignin obtained after alkaline treatment of steamexploded sugarcane bagasse was submitted to an acidification process. The soluble fractions produced at different pH values were comprehensively characterized and in vitro antioxidant capacity against r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 64 publications
1
16
1
2
Order By: Relevance
“…Several studies have showed that lignin can serve as a renewable source of aromatic compounds with antioxidant capacity [5][6][7][8][9][10]. However, the antioxidant capacity of lignins, as well as their physicochemical properties, significantly depends on the source of lignocellulosic material and extraction method employed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have showed that lignin can serve as a renewable source of aromatic compounds with antioxidant capacity [5][6][7][8][9][10]. However, the antioxidant capacity of lignins, as well as their physicochemical properties, significantly depends on the source of lignocellulosic material and extraction method employed.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the relative activity remained as high as 60% and 40% after prolonged incubation (24 h) in pH 8.0 and 9.0, respectively. This feature could be useful for conversion of lignin streams derived from biorefineries; for instance, Brenelli et al described a fractionation process based on acidification steps, starting from lignin derived alkaline treatment of steam-exploded sugarcane bagasse, that resulted on soluble fractions of pH 8.0 and 9.0 containing FA [69]. According the study, the pH of soluble fractions containing FA show not only pH 8.0 (9.0) but also pH 4.0, 6.0, and 10.0 [69].…”
Section: Resultsmentioning
confidence: 99%
“…The GPC gradient was performed isocratically using NaOH 0.1 mol l −1 as the eluent at a 0.5 ml min −1 flow rate and 20 °C. For each supernatant, 500 µl was diluted in 500 µl of NaOH 0.1 mol l −1 prior to injection [ 8 ]. The lignin fragments were detected by a UV detector (280 nm) and the molecular weights were determined using different polyphenolic compounds as external standards.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled deconstruction of the macromolecule to produce lower molecular weight compounds is critical in lignin valorization strategies [ 5 , 7 ]. Nevertheless, examples of chemical depolymerization or acidification treatment of lignin to produce low-molecular-weight aromatic compounds have proven to be methods of interest for adding value to lignin streams [ 8 10 ]. The depolymerization of lignin into monomers such as guaiacyl, syringyl, vanillin, and syringaldehyde is of commercial interest due to the potential for application of these molecules in the biofuel, food, cosmetic, and other industrial sectors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%